Screening of Psychiatric Patients for Hypovitaminosis B12. Issue 5670 (6th September 1969) - Murphy, F.; Srivastava, P. C.; Varadi, S.; Elwis, A.
Abstract : Vitamin B12 assays and inspection of peripheral blood films performed on 1, 004 consecutive new patients over the age of 50 admitted to mental hospital led to the discovery of pernicious anaemia in only two cases. It is concluded that routine vitamin B12 assays are justified only when fully-automated techniques have become available.